Voluntary wheel running reveals sex-specific nociceptive factors in murine experimental autoimmune encephalomyelitis. Issue 4 (April 2019) - Mifflin, Katherine A.; Yousuf, Muhammad S.; Thorburn, Kevin C.; Huang, Jennifer.; Pérez-Muñoz, Maria Elisa; Tenorio, Gustavo; Walter, Jens; Ballanyi, Klaus; Drohomyrecky, Paulina C.; Dunn, Shannon E.; Kerr, Bradley J.
Abstract : Abstract: Multiple sclerosis (MS) is an inflammatory, neurodegenerative autoimmune disease associated with sensory and motor dysfunction. Although estimates vary, ∼50% of patients with MS experience pain during their disease. The mechanisms underlying the development of pain are not fully understood, and no effective treatment for MS-related pain is available. Previous work from our laboratory demonstrated that voluntary exercise (wheel running) can reduce nociceptive behaviours at the disease onset in female mice with experimental autoimmune encephalomyelitis (EAE), an animal model used to study the immunopathogenesis of MS. However, given the established sex differences in the underlying mechanisms of chronic pain and MS, we wanted to investigate whether wheel running would also be effective at preventing nociceptive behaviours in male mice with EAE. C57BL/6 mice of both sexes were given access to running wheels for 1 hour/day until the disease onset, when nociceptive behaviour was assessed using von Frey hairs. Daily running effectively reduced nociceptive behaviour in female mice, but not in male mice. We explored the potential biological mechanisms for these effects and found that the reduction in nociceptive behaviour in female mice was associated with reduced levels of inflammatory cytokines from myelin-reactive T cells as well as reduced dorsal root ganglia excitability as seen by decreased calcium responses. These changes were not seen in male mice. Instead, running increased the levels of inflammatory cytokines and potentiated Ca 2+ responses in dorsal root ganglia cells. Our results show that voluntary wheel running has sex-dependent effects on nociceptive behaviour and inflammatory responses in male and female mice with EAE. Abstract : Voluntary wheel running decreases nociceptive hypersensitivity associated with experimental autoimmune encephalomyelitis in a sex-specific manner and is associated with sex-specific effects on peripheral cytokine production.